76th issue Info Kampus UiTM Sarawak Bulletin July 2018 - Amir Abdullah, Ardiana Mazwa Raudah; Chin, Ch'ng Looi; Yeo, Jacinta Jiin Yih (UiTM Sarawak, 2018)
As such, UiTM Sarawak, which is supporting this effort, plans to upgrade itself into a smart campus as part of its initiative to support the state’s vision of digital development. This move is in line with the state government’s effort to turn Kuching into a smart city. To embrace a digital economy, digital knowledge and cyber security are important. Therefore, UiTM Sarawak with UiTM Sarawak Alumni Association (MITSA) and Cybersecurity Malaysia jointly organised ‘Ops Jelajah Cyber’ Sarawak edition. This shows that UiTM Sarawak is committed to support the State Government in the successful implementation of a digital economy in the state